Integrating Universal Design for Learning and Individualized Education Plans in Inclusive Education: A Systematic Literature Review - Siti Rokhmah Sobariah; Budi Susetyo; Iding Tarsidi; Eka Yuli Astuti; Ezza Mad Baguri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
Inclusive education requires curriculum frameworks that accommodate learner diversity while ensuring individualized support for students with special educational needs. Although Universal Design for Learning (UDL) and Individualized Education Plans (IEPs) are widely recognized as complementary approaches, evidence regarding their integration within inclusive curriculum design remains fragmented. This study aims to synthesize research trends, implementation patterns, empirical impacts, and challenges associated with the integration of UDL and IEPs in inclusive education. A Systematic Literature Review (SLR) was conducted following the framework of Denyer and Tranfield (2009) and PRISMA guidelines. Literature published between 2015 and 2025 was retrieved from Scopus, Web of Science, ERIC, SpringerLink, Taylor & Francis, and Google Scholar. After a rigorous screening and quality appraisal process using CASP and JBI instruments, ten high-quality studies were included in the final synthesis. The findings reveal that UDL consistently enhances learning accessibility, student engagement, and academic achievement through flexible instructional design and multimodal learning opportunities. However, the integration of UDL and IEPs remains largely fragmented and is rarely institutionalized within formal curriculum policies. Successful implementation is supported by professional development, collaborative practices among educators, strong school leadership, and access to educational technology, while administrative burdens and limited policy alignment remain significant barriers. This review highlights the need for a systemic framework that integrates universal curriculum design with individualized planning to strengthen sustainable inclusive education practices.